(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Burn is one of the common conditions affected by individuals in day-to-day activity which needs extra attention to prevent ugly scars and many more complications. Ayurveda has a wide range of herbal formulations to manage such types of burn wounds. Among them, one is Madhuchistadi Ghrita which has burn wound healing properties by its Vrana Ropana drugs. A 45-year-old male patient suffered second-degree scald burn along with blisters and burning over the right hand for four days. The patient was successfully treated with a local application of Madhuchistadi Ghrita twice daily for 15 days. After seven days of treatment, the wound was 70% covered with epithelialization and at the end of 15 days, the wound was completely healed. During the follow-up period of 1 month, the skin was completely remodeled with the presence of skin appendages. This is a single case report with a positive outcome on the treatment of second-degree scald burns with the application of Madhuchistadi Ghrita.